Pengaruh Disiplin Kerja Dan K3 Terhadap Kinerja Karyawan Pada PT. Perkebunan Minanga Ogan: (Studi Kasus Pada karyawan PKS SENM) - wiranawata, hilmi (Pusat Riset dan Inovasi Nasional, 2024)
This study aimed to determine the influence of work discipline and K3 (Occupational Safety and Health) on employees' performance at PT. Minanga Ogan Plantation (a case study on PKS SENM employees). The data analysis technique used was Multiple Linear Regression. Based on the results of the partial analysis of the discipline variable, it showed that there was a significant influence of work discipline on employees' performance with a t-count value of 3,851. and the K3 variable showed that there was a significant influence of K3 on employees' with t-count value of 7,654. Simultaneously, it was found that there was a jointly significant influence between work discipline and K3 on employee performance at PT. Minanga Ogan Plantation with an f-count value of 79,052. the coefficient of determination (R2) obtained was 0.640. This meant that the contribution of work discipline and K3 (Occupational Safety and Health) to employees' performance was 64% while the remaining 36% was influenced by other variables outside of this study.